Comunicação táctil para todo público: sistema braille usando verniz poli(metacrilato de metila) em relevo polimerizável por ultravioleta (UV) impresso junto com texto e imagens em tinta (i-Br/Vza-UVxmf) - Sanclemente, José Manuel Hernández (2011)
This paper presents an innovation (invention) that is applied as a tool for education inclusion and of accessibility among visually impaired people, representing 6.98% of the Brazilian population. The simultaneous printing using the Braille system along with its equivalent in Portuguese (or any other language) is proposed. A text printed in Portuguese (e.g., using offset printing) will then be printed in Braille applied using acrylic varnish that is dried with ultraviolet (UV) rays. This printing approach has been named i-Br/Vza-UVxmf and may be present in packages or publishing products. The proposed system eliminates the use of micro-holes left by traditional printing in Braille. Moreover, the system of micro-holes presents the risk of contamination (or the passage of contaminating substances) in the case of food packaging, personal use or cleansing items, which will not happen in the i-Br/Vza-UVxmf process. Since the proposed process can be applied to any editorial product (as a document, book or package), this printed material will be useful either to the normal sighted (who will read the material printed in Portuguese) as the visually impaired (who read Braille thanks to the embossing generated by the acrylic varnish). It’s Tiflotegnologics the art and Technique to write and editing for impaired people Then, this approach is intended to facilitate the living and the relationship among visually impaired and normal sighted people; leading them to better living and education standards. Moreover, this study may contribute to the implementation of existing legislation that requires the disclosure of information on medicine, food, personal use or cleansing items packaging. Current legislation demands the communication of name, content, specifications and expiration date of products. Finally, normal sighted people can benefit from the proposed system, making use of the fact that the material is printed in Portuguese and in Braille; and making them familiar with the use of tactile communication(written in Braille).